Arrowroot (Maranta arundinacea L.) Tuber Extract Modulated Gut Microbiota and Improved Glycemic Control in Type 2 Diabetic Mice - Pangastuti, Artini; Anggraini, Putri Regita; Listyawati, Shanti; Sari, Siti Lusi Arum (Bogor Agricultural University, Indonesia, 2026)
Type 2 diabetes mellitus (T2DM) is a metabolic disorder characterized by hyperglycemia and has become a global health concern. Gut microbiota alterations significantly influence diabetes onset, which can be mitigated through prebiotic intake. Arrowroot tubers (Maranta arundinacea L.) possess prebiotic potential due to their oligosaccharide and dietary fiber content. This study evaluated the effects of arrowroot tuber extract on blood glucose, glucose tolerance, and gut microbiota composition in a T2DM mouse model. Tubers were macerated in ethanol, and BALB/c mice were fed a high-fat diet for five weeks, followed by streptozotocin injection (35 mg/kg) to induce T2DM. Mice received 150 mg of arrowroot tuber extract orally for 28 days. Blood glucose levels were measured on days 0, 14, and 28, and an oral glucose tolerance test (OGTT) was performed. Cecal samples collected after four weeks underwent 16S rRNA sequencing, and data were analyzed using One-Way ANOVA (p<0.05). Treatment with arrowroot tuber extract for 28 days reduced blood glucose levels by 40.5% and improved glucose tolerance. The extract modulated gut microbiota, decreasing harmful bacteria while increasing short-chain fatty acid (SCFA)-producing genera such as Lachnospiraceae NK4A136, Ligilactobacillus, and Alistipes. These results indicate that arrowroot tuber extract can beneficially alter gut microbiota composition and ameliorate hyperglycemia, suggesting its potential as a prebiotic-based therapeutic strategy for managing T2DM.